1988
DOI: 10.1002/ijc.2910410318
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of prolonged administration of cysteamine on experimental carcinogenesis in rat stomach induced by N‐methyl‐N′‐nitro‐N‐nitrosoguanidine

Abstract: The effect of cysteamine (2-aminoethanethiol hydrochloride) on the incidence and histology of gastric adenocarcinomas induced by N-methyl-N'-nitro-N-nitrosoguanidine (MNNG) was investigated in inbred Wistar rats. Prolonged administration of 25 or 50 mg per kg body weight of cysteamine after treatment with MNNG for 25 weeks significantly reduced the incidence and number of adenocarcinomas of the glandular stomach. Histological examination showed that the adenocarcinomas that did develop in rats treated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…Watanabe et al (1992) found that oral administration of NaCl after MNNG pretreatment significantly increased the incidence of gastric cancers and that it also significantly increased the height of the pyloric mucosa. Many investigators (Takahashi et al, 1986;Tatsuta et al, 1988a;Kobori et al, 1984) have indicated that enhancing effects on gastric carcinogenesis may be related to stimulation of cell proliferation and elongation of the mucosa. These findings suggest that a non-genotoxic component increases tumour yield when administered subsequent to a genotoxic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Watanabe et al (1992) found that oral administration of NaCl after MNNG pretreatment significantly increased the incidence of gastric cancers and that it also significantly increased the height of the pyloric mucosa. Many investigators (Takahashi et al, 1986;Tatsuta et al, 1988a;Kobori et al, 1984) have indicated that enhancing effects on gastric carcinogenesis may be related to stimulation of cell proliferation and elongation of the mucosa. These findings suggest that a non-genotoxic component increases tumour yield when administered subsequent to a genotoxic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Starting at 3 weeks of age, rats were given drinking water containing MNNG at a concentration of 50 g/mL for 25 weeks. The MNNG solution was supplied from bottles covered with aluminum foil to prevent photolysis and refilled every other day as reported previously (30). After 25 weeks, MNNG administration was stopped, and normal tap water was supplied.…”
Section: Methodsmentioning
confidence: 99%
“…Oral administration of high dose phenylalanine significantly increased the basal serum gastrin level and significantly decreased the norepinephrine concentration in the antral portion of the gastric wall, as well as the labelling indices of antral mucosa. These findings indicate that orally administered phenylalanine inhibits the development of gastric cancers.Gastrointestinal regulatory peptides, such as vasoactive intestinal peptide (lishi et al, 1987), secretin (Howatson & Carter, 1987), cholecystokinin and its analogue (Satake et al, 1986), and gastrin (Tatsuta et al, 1977b), have been found to regulate development of cancers of the gastrointestinal tract and the pancreas. We recently found that prolonged alternate-day administration of the potent duodenal ulcerogen cysteamine after 25 weeks of N-methyl-N'-nitro-Nnitrosoguanidine (MNNG) treatment led to marked hypergastrinaemia and also to significant protection against the development of gastric cancers (Tatsuta et al, 1988a).…”
mentioning
confidence: 99%